Modulation of ovarian response in anoestrus cattle treated with insulin alone and in combination with gonadotropin releasing hormone - SHUKLA, S N; AGARWAL, S K; SHANKER, U; VARSHNEY, V P; MAJUMDAR, A C (The Indian Journal of Animal Reproduction, 2023)
The influence of insulin alone and in combination with gonadotropin releasing hormone (GnRH) on ovarian responseas well as glucose and progesterone-profile was studied on 28 anoestrus cows divided randomly into 4 groups i.e. insulin treatment(G-1), GnRH treatment (G-11), insulin plus GnRH (G-111) and control (G-IV);- each comprising 7 aeim.alli lu insu..li.n treatmentgroup cows were injected subcutaneously long acting purified bovine insulin at 0.25 JU/leg body weight/day for 5 consecutive days.In GnRH treatment group cows were injected intramuscularly single IO μg dose of busereline acetate. In insulin + GnRH treatmentgroup cows were injected insulin for 5 days similar lo G-1 and a single injection of GnRH 48 hrs after the last insulin injection. Incontrol group cows were not administered any drug. The induction of estrus was higher in insulin treated cows (85.7%) (P
Keywords: Anoestrus; cattle; insulin; GnRH; plasma glucose; serum progestrone